Determinan Tax Avoidance pada Perusahaan Subsektor Pertanian: Peran Profitabilitas dan Inventory Intensity - Wendra Afriana; Mujiyani Mujiyani; Erna Kustyarini; Lasminiasih Lasminiasih (Journal of Business and Economics Research (JBE), 2026)
This study aims to analyze the effect of profitability and inventory intensity on tax avoidance in palm oil plantation sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Tax avoidance refers to a company's efforts to minimize its tax burden by exploiting loopholes within existing tax regulations. This practice has become a significant concern because it has the potential to reduce government tax revenues, particularly in the palm oil plantation sector, which makes a substantial contribution to the national economy. Profitability is proxied by Return on Assets (ROA), while inventory intensity is measured by the proportion of inventory to total assets. This research employs a quantitative approach using secondary data obtained from the financial statements of palm oil plantation sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The sample was selected using a purposive sampling technique, resulting in several companies that met the research criteria. Data analysis was conducted using panel data regression with the assistance of EViews 13 software. Model selection was carried out through the Chow Test, Hausman Test, and Lagrange Multiplier Test, which indicated that the Random Effect Model (REM) was the most appropriate model for this study. The results show that, partially, profitability (ROA) has a negative and significant effect on tax avoidance, while inventory intensity has no significant effect on tax avoidance. Simultaneously, profitability and inventory intensity have a significant effect on tax avoidance. Furthermore, the coefficient of determination test indicates that the two independent variables explain 35.23% of the variation in tax avoidance, while the remaining 64.77% is influenced by other factors outside the research model. This study provides an empirical contribution by extending the literature on the determinants of tax avoidance in palm oil plantation sub-sector companies and providing evidence that profitability is a more dominant factor than inventory intensity in influencing tax avoidance practices.